Being an environmentalist among Catholics ... The School of Integral Ecology Leaders and Other Initiatives of the St. Francis of Assisi Ecological Movement (REFA) - Ślimko, Emilia; Jaromi, Stanisław (Studia Ecologiae et Bioethicae, 2020)
This study provides a summary description of the abundant activities of the St. Francis of Assisi Ecological Movement (REFA), which emerged over 30 years ago in the environment of Polish Franciscans and which ever since has been propagating the idea of engaging Christians in environmental protection issues. REFA’s motto is “Catholics among ecologists, environmentalists among Catholics.” In its activity, REFA has undertaken many different pro-environmental initiatives and implemented many ecological projects, part of which are presented in this study.